Nine years of Communist Party of India. - Supporters of Hindustani Ghadar Party, Organization of Indian Marxist-Leninists Abroad :::Creator::::::::::::
Poster announcing public meeting to celebrate nine years of Communist Party of India (Marxist - Leninist) held at Barrows Hall in U.C. Berkeley.